Time‐Series Analysis of Volume Change at Brady Hot Springs, Nevada, USA, Using Geodetic Data From 2003–2018. Issue 9 (27th August 2020) - Reinisch, Elena C.; Cardiff, Michael; Kreemer, Corné; Akerley, John; Feigl, Kurt L.
Abstract: Brady Hot Springs geothermal field has exhibited subsidence, as measured by interferometric synthetic aperture radar (InSAR). Previous studies have examined both the temporal evolution of the deformation from 2004 through 2016 and the spatial extent of the deformation, directly relating the observed subsidence to volumetric changes below the surface. We extend the modeling at Brady to analyze a data set of interferometric pairs spanning from the end of 2003 through 2018. We examine spatial and temporal trends in the observed deformation by time‐series analysis of each of the 1, 656 cubic voxels in a parameterized elastic dislocation model to identify areas where the subsurface volume changes as a function of time. Joint time‐series analysis of Global Positioning System and InSAR pairs confirm significant changes in rates of volume change during time intervals when well operations were varied. The rate of subsidence increases with increased injection, consistent with the identification of thermal contraction of the rock matrix as the dominant driving mechanism. Conversely, the modeled volume increases when pumping ceases, suggesting thermal expansion of the rock matrix. Key Points: GPS and InSAR data show temporal variations in subsidence rate Spatial distribution of deformation is described by "multicube" elastic dislocation model of thermal contraction Temporal variations are related to changes in pumping by the power plant at Brady Hot Springs, Nevada, USA